Pharmacogenomic testing: aiding in the management of psychotropic therapy for adolescents with autism spectrum disorders - Bose-Brill S; Xing J; Barnette DJ; Hanks C (Dove Medical Press, 2017)
Seuli Bose-Brill,1 Jinming Xing,2 Debra J Barnette,1,2 Christopher Hanks1 1Internal Medicine and Pediatrics at Grandview, Wexner Medical Center, 2Department of Practice and Science, College of Pharmacy, The Ohio State University, Columbus, OH, USA Abstract: Adolescents with autism have higher rates of anxiety than the general adolescent population. They often struggle to express psychological symptoms verbally where their symptoms may manifest as withdrawal and agitation. Adolescent patients with autism have higher rates of polypharmacy and high-risk psychiatric medication use (eg, atypical antipsychotics) than other patients with psychiatric illness. Primary care pediatricians are at the front lines of psychiatric management for patients with autism. Yet, they have inadequate access to pediatric psychiatry for complex medication management. Pharmacogenomic testing can provide personalized drug metabolism profiles for a majority of psychotropic medications. Primary care based pharmacogenomic testing for adolescents with autism on one or more psychiatric medications may help individualize and optimize complex medication regimens, while promoting drug safety. Keywords: autism, pharmacogenomic, pharmacogenetic, pharmacotherapy, anxiety, depression, psychiatry, pediatrics